A nonenveloped virus with a lipid envelope: hepatitis A virus as used in virus‐reduction studies. Issue 6 (28th March 2017) - Kapsch, Anna‐Maria; Farcet, Maria R.; Antoine, Gerhard; Kreil, Thomas R.
Abstract : BACKGROUND: Recently, a quasi‐lipid–enveloped (LE) form of the traditionally nonlipid‐enveloped (NLE) hepatitis A virus (HAV) was described in human serum and cell culture‐derived HAV stocks. This discovery challenges the understanding of HAV reduction in virus clearance studies of plasma products, which were performed under the premise of an NLE nature of this virus. Here, the presence of LE particles in HAV stocks used for reduction studies was verified, and the hypothesis that LE and NLE particles might contribute to the differential heat sensitivity of HAV variants during heat treatment of human serum albumin was evaluated. STUDY DESIGN AND METHODS: Cell culture lysates and supernatants of two cytopathic HAV variants, HM175/18f and HM175/24a, were characterized for their LE and NLE particle content by isopycnic gradient centrifugation. The obtained fractions were characterized for relative infectivity and then subjected to heat treatment (58.0 ± 1.0°C for 590 ± 10 minutes) in 12.5% human serum albumin to investigate their respective heat sensitivity. RESULTS: Preparations of the two HAV variants contained either LE particles (HM175/24a) or LE and NLE particles (HM175/18f) with equivalent specific infectivity. For HM175/18f, heat sensitivity of LE and NLE fractions did not differ significantly, and inactivation of the whole virus stock was identical to the NLE particle inactivation profile, whereas the HM175/24a variant was more heat sensitive. CONCLUSION: The results indicate that, in heat‐treatment studies, the LE or NLE HAV phenotype is less important than the choice of HAV variant, and the most heat‐resistant HM175/18f should be used.